Distribution of Potentially Pathogenic Vibrio parahaemolyticus in Seafood and the Aquatic Environment of Mumbai, India - Ayyappan, Minimol V.; Balange, Amjad K.; Nayak, Binaya Bhusan; Kumar, Sanath (Fishery Technology, 2018)
The occurrence of total and pathogenic Vibrio parahaemolyticus in fresh seafood and the coastal environment of Mumbai, India was examined in this study. Samples comprising of fish, shellfish, coastal sediment and coastal waters were analyzed for V. parahaemolyticus by selective enrichment and isolation. Biochemically identified isolates were tested for the presence of tlh (thermolabile hemolysin), tdh (thermostable direct hemolysin) and trh (tdh-related hemolysin) by polymerase chain reaction (PCR). While Chromogenic Vibrio (CV) agar yielded V. parhaemolyticus from all samples (100%), TCBS agar yielded V. parahaemolyticus from 57.1% of the samples. The incidence of trh+ V. parahaemolyticus was high, being isolated from 16.4% of the samples analyzed, while the tdh+ V. parahaemolyticus were isolated from 1.4% of samples. Two tdh-, trh+ isolates from the coastal water were positive by a in pandemic group-specific (GS) PCR. The study suggests that seafood and coastal environment may harbor pathogenic V. parahaemolyticus with characteristics of pandemic clones, although their incidence is very low. Further, sodium taurocholate (ST) broth and chromogenic Vibrio (CV) agar combination is highly suitable for the isolation of total and pathogenic V. parahaemolyticus from seafood and environmental samples.